Basic income: confusion, claims and choices. (26th October 2018) - Piachaud, David
Abstract : Basic Income is gaining increasing prominence. The paper analyses the idea. Six confusions are discussed and suggestions made for greater clarity. Five claims made for Basic Income are considered – that unconditionality is just, that individualised simplicity is fair, that it is economically efficient, that it is compatible with the future labour market, and is politically feasible. All five of these claims are found to be wanting. Some of the choices that must be made in developing policy to reduce poverty are reviewed. The paper concludes that if the aim is to tackle poverty, Basic Income is not the solution.